Analysis of Productivity Levels of Human Capital Investment in the Perspective of Education for Jenderal Soedirman University Graduated - Sofiatul Khotimah; Meutia Karunia Dewi; Siti Aenandari Hadatul Aysi (South Sulawesi Education Development (SSED), 2024)
The purpose of this study was to determine the effect of productivity levels in human capital investment in achievement, organization, and training on the work of graduates of Jenderal Sudirman University. The type of research used is quantitative research with multiple linear regression analysis, where the researcher analyzes the influence between several independent variables (independent variables) and the dependent variable (bound variable). The results showed that the productivity levels influence student achievement at Jenderal Sudirman University and did not affect the achievement of human capital investment based on job readiness and performance. The level of productivity in the organization and training influences the achievements of human capital investment in terms of readiness and job performance. While the other analysis obtained the results that the variables of achievement, organization and training together have a positive effect on the work variable. This is evidenced by the analysis results that are 8,278 (F-count) > 2.76 (F-table) and the significance value is 0.000 < 0.05.